German labor emigration in times of technological change : occupational characteristics and geographical patterns - Décieux, Jean Philippe; Mergener, Alexandra (My University, 2021)
"Technological change has altered labor market demands within well-developed societies implying global competition for skilled labor and, as a consequence, new forms of labor migration. So far, patterns of this labor migration have been underexplored. Thus, the article analyzes characteristics, geographies and possible underlying drivers of workers migrating from Germany as an exemplary case for a well-developed country. Relying on probability-based and unique data, our findings reveal that, besides demand for people with higher levels of education, performing specific occupational tasks is also in demand in the global competition for talent. Hence, Germans in jobs with a high proportion of analytical non-routine tasks are more likely to emigrate than those with predominantly manual routine tasks. Moreover, the results show that global discrepancies concerning the technological development between the country of origin and the country to which they emigrate are a crucial contextual driver attracting this specifically demanded work force. Workers mainly performing analytical non-routine tasks within their job tend to move to countries which are technologically more developed than Germany while individuals performing jobs with a high share of non-routine manual or interactive tasks tend to emigrate to countries that are less technologically developed than Germany." (Author's abstract ; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; I 2.1 Deutschland; Arbeitsmigration; Arbeitsmarkt; Industrieländer; Fachkräfte; Digitalkompetenz; Kreativität; Routinetätigkeit; BIBB-/BAuA-Erhebung; Sozioökonomisches Panel; German Emigration and Remigration Panel Study; Bundesrepublik Deutschland